Archaeological Parks and Land Development: Insights on "Guidelines for Constitution and Value Enhancement of Archeological Parks" (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
This paper aims to illustrate the contents of Guidelines for constitution and value enhancement of Archeological Parks, issued by DM on 18th April 2012 and published on 2nd August (regular supplement 65 of Gazzetta Ufficiale 179). The preliminary steps to create an archaeological park concern the evaluation of the archaeological contents and the potential of the area; then scientific projects will be carried out and the legal/institutional aspects and economic/financial aspects will be duly defined and organized. The scientific projects indispensable for the organization of a park regard archaeology and landscaping, in terms of naturalistic/environmental and architectonic/urbanistic features. The features of the parks will be defined together with their relations to the territorial planning, and subsequently the aspects of protection and value enhancement will be addressed, together with the contents of communication. The last point for the executive phase is the definition of the legal institutional aspect; the process should be concluded with the accrediting procedure.
Keywords: Archaeological Parks; Archaeology; Landscape; Value enhancement; Communication; Management